Experimental investigation on the spatial differences of hydrate dissociation by depressurization in water-saturated methane hydrate reservoirs. (15th May 2021) - Cui, Jinlong; Li, Kun; Cheng, Liwei; Li, Qingping; Sun, Zhenfeng; Xiao, Peng; Li, Xingxun; Chen, Guangjin; Sun, Changyu
Highlights: Spatial differences of hydrate dissociation in the reservoir were investigated. Factors affecting spatial differences of hydrate dissociation were investigated. Factors controlling hydrate dissociation were analyzed. The vacating of pore spaces is the controlling factor of hydrate dissociation. A new method to enhance gas production from marine gas hydrate was proposed. Abstract: To improve the exploitation efficiency of future commercial marine natural gas hydrate, it is of critical significance to have a solid understanding of the spatial differences of hydrate dissociation. However, few studies have investigated this topic. In this study, a novel L-shape Hydrate Simulator (LHS) with a vertical vessel and a horizontal vessel was established and used to investigate the spatial differences of hydrate dissociation in water-saturated methane hydrate samples by depressurization. It was amazingly found that the hydrate dissociation was abnormally much faster in the location far from the mining well with the highest pressure than in the location near the mining well with the lowest pressure in the vertical vessel. This abnormal phenomenon was caused by the earliest uneven vacating of pore spaces in the vertical vessel. This phenomenon was not obvious in the horizontal vessel as there was little difference in the pore spaces vacating rates in different locations. The pressure reduction leaded to faster hydrate dissociation near the mining well in the horizontal vessel. The experiments on sediments with different permeability indicated that the sediments with higher permeability showed more pronounced spatial difference of hydrate dissociation, and the presence of clay (montmorillonite) in the sediments had significant impacts on the spatial difference of hydrate dissociation. The results in this study demonstrate that vacating of pore spaces of sediments is of determining significance for increasing hydrate dissociation rate in water-saturated sediments and provide important implications for developing methods to enhance the gas production from marine hydrate deposits.